The effects of demineralisation and sampling point variability on the measurement of glutamine deamidation in type I collagen extracted from bone. (May 2016) - Simpson, J.P.; Penkman, K.E.H.; Demarchi, B.; Koon, H.; Collins, M.J.; Thomas-Oates, J.; Shapiro, B.; Stark, M.; Wilson, J.
Abstract: The level of glutamine (Gln) deamidation in bone collagen provides information on the diagenetic history of bone but, in order to accurately assess the extent of Gln deamidation, it is important to minimise the conditions that may induce deamidation during the sample preparation. Here we report the results of a preliminary investigation of the variability in glutamine deamidation levels in an archaeological bone due to: a) sampling location within a bone; b) localised diagenesis; and c) sample preparation methods. We then investigate the effects of pre-treatment on three bone samples: one modern, one Medieval and one Pleistocene. The treatment of bone with acidic solutions was found to both induce deamidation and break down the collagen fibril structure. This is particularly evident in the Pleistocene material (∼80, 000 years BP) considered in this study. We show that ethylenediaminetetraacetic acid (EDTA), when used as an alternative to hydrochloric acid (HCl) demineralisation, induces minimal levels of deamidation and maintains the collagen fibril structure. Areas of bone exhibiting localised degradation are shown to be correlated with an increase in the levels of Gln deamidation. This indicates that the extent of Gln deamidation could provide a marker for diagenesis but that sampling is important, and that, whenever possible, subsamples should be taken from areas of the bone that are visually representative of the bone as a whole. Although validation of our observations will require analysis of a larger sample set, deamidation measurements could be a valuable screening tool to evaluate the suitability of bone for further destructive collagen analyses such as isotopic or DNA analysis, as well as assessing the overall preservation of bone material at a site. The measure of bone preservation may be useful to help conservators identify bones that may require special long-term storage conditions. Highlights: Glutamine deamidation may be a useful marker for collagen preservation in bone. Deamidation could be used to screen bone prior to further destructive analysis. Deamidation could help conservators identify artefacts at risk of deterioration. Older bone is more likely to be susceptible to acid-induced deamidation. EDTA demineralisation helps extract collagen from older bones with minimal damage.